Missionaries and Empire: British Imperialism through the Lens of Indian Christian Experiences - Nazish Safdar,; Dr. Farhat Jabeen Virk, (Al-Qanṭara, 2024)
This study examines the subtle differences between imperialism and colonialism, with a specific emphasis on the British rule in India and how it affected the Christian population in the region. Imperialism involves a wider plan to assert dominance in different ways, whereas colonialism involves direct control and settlement in foreign lands. During the late 19th and early 20th centuries, British imperialism in India, based on economic interests and cultural superiority, had a profound impact on the country's social, economic, and political structures. The research focuses on Jaye Ali Bakhsh's travel narrative, "Safar-e-Dakan," showcasing how cultural hegemony and foreign beliefs are enforced, especially through missionary work. It shows how British actions worsened famines and restricted opportunities for Indians, including Christians, in the colonial administration. In conclusion, the study highlights the enduring impacts of British imperialism, demonstrating the intricacies of cultural assimilation and the social and political obstacles encountered by the indigenous Christian population in post-colonial India.